OBJEK PENDIDIKAN MENURUT PERSPEKTIF AL-QURAN - Siti Aisyah (JURNAL PUSAKA, 2022)
Al-Quran is more deeply an obligation for all Muslims. Of course, the purpose and purpose of studying the Qur'an is to understand and master more deeply the nature and rules of law in it. It is Allah's desire that all changes must be guided by the shade of the Qur'an, under his inspiration, so that the changes lead to the good, as the nature of the Qur'an. Al-Quran is more deeply an obligation for all Muslims. Of course, the purpose and purpose of studying the Qur'an is to understand and master more deeply the nature and rules of law in it.